(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The field of historical linguistics has undergone significant transformation with the inception of corpus linguistics, which has provided a systematic and empirical approach to analysing language change over time. Traditional methods of historical language analysis were reliant on limited texts and impressions, but the development and availability of large, digitized corpora have enabled linguists to draw upon extensive bodies of authentic language. This approach illuminates patterns and trends that were previously inaccessible, offering insights into the evolution of vocabulary, syntax, morphology, and semantics.